Eine generelle Finanztransaktionssteuer: Konzept, Begründung, Auswirkungen - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2009)
– Initially this paper outlines the concept of a tax on all transactions to do with financial assets. It summarises the main arguments for and against such a tax. The next part documents the relevant empirical evidence necessary to be able to evaluate the arguments. In particular the development of financial transactions is documented, as well as the dynamic of exchange rates, raw material prices and share prices. The data would suggest that the introduction of a financial transaction tax would reduce the instability of such prices. Indeed it would reduce not only its short term volatility but also the longer term upwards and downwards trends ("bull markets" and "bear markets"). Finally the potential revenue of a transaction tax is estimated for three different rates of tax (0,1 percent, 0,05 percent and 0,01 percent). Due to the high trading volumes on the financial markets the revenue from such a tax would be considerable: with a tax rate of 0.05 percent the revenues in Germany were between 0.7 percent and 1.5 percent of GDP and in Europe between 0.9 percent and 2.1 percent.
Keywords: 330; Finanztransaktionen; Spekulationstechniken; Dynamik von Vermögenspreisen; Transaktionssteuern; Spekulation; Tobinsteuer; Steuereinnahmen; Steuerwirkung; Welt